Disparities in Prenatal Immunization Rates in Rural and Urban US Areas by Indicators of Access to Care. Issue 1 (14th February 2022) - Kaur, Ravneet; Callaghan, Timothy; Regan, Annette K.
Abstract: Purpose: To evaluate disparities in urban‐rural immunization rates among pregnant women by indicators of access to health care. Methods: We analyzed Phase 8 (2016‐2018) Pregnant Risk Assessment Monitoring System data for 82, 603 respondents who recently gave birth to a live infant. Uptake of influenza (33 states) or Tdap (19 states) vaccines was compared for rural versus urban areas of participating states. We compared the prevalence of immunization for rural versus urban areas by indicators of health care access using average marginal predictive values from multivariable regression models. Findings: Although nearly half (48.2%) of pregnant women in rural areas relied on Medicaid to fund prenatal care, rural‐residing women were less likely to live in a state offering full coverage under Medicaid to pregnant women than urban‐residing women (93.9% vs 98.0%, respectively). Among states with Medicaid programs not offering full access for pregnant women, influenza immunization coverage was 12% lower (aPR 0.88; 95% CI 0.82, 0.94) and Tdap immunization coverage was 20% lower (aPR 0.80; 95% CI 0.68, 0.95) for rural versus urban areas. Uninsured women in rural areas were less likely to receive influenza or Tdap vaccine compared to uninsured women in urban areas (aPR 0.65; 95% CI 0.50, 0.85 and aPR 0.73; 95% CI 0.57, 0.95, respectively). Conclusions: Pregnant women residing in rural areas more commonly rely on Medicaid to financially support prenatal care but are less likely to have expanded or full access to Medicaid coverage, potentially contributing to disparities vaccine uptake during pregnancy and increased rates of vaccine‐preventable disease.